RENEWAL CONCEPT OF ISLAM AND ITS URGENCY IN ADVANCING ISLAMIC CIVILIZATION IN INDONESIA ACCORDING TO HARUN NASUTION - Ihwan Agustono (Journal of Islamic Studies and Humanities, 2023)
This article intends to examine the concept of rational theological concepts in Islam with a focus on the thoughts of Harun Nasution. Harun Nasution is a controversial Islamic reformer. His idea was born as a response to and against the traditional ideas that developed at that time; even Harun Nasution dared to go against the flow of traditional ethics that according to him had long been rusty and difficult to remove. The emphasis of this paper is on the presentation of Harun Nasution's progressive thinking in the Islamic theological concept and tts importance in advancing Indonesian Islamic civilization. Thus, the qualitative method will be employed in this work, along with a historical study approach gleaned from books, journals, and related publications. The essence of Harun Nasution’s theory is the realization that Islam is a universal rational religion, and that via rational theology, people can fully comprehend the meaning of revelation in both the Qur'an and the Hadith. To build the Islamic Ummah such that it always exists exclusively through forming a rational society, a renewal movement through education is required.